To the freeholders, freemen, and inhabitants, of the city and county of New-York : Gentlemen, As a report prevails, that the ship Beulah, is destined for Halifax, I have perused the association of the Congress, in order to satisfy myself, whether her going there, will be conformable to their intention: I think it will not . - Citizen, active 1775 (LLMC-digital (Series), 1775)
Concerning a possible violation of the non-importation agreement.